Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Pembelajaran Kimia Penyetaraan Reaksi Redoks Melalui Lesson Study Di Kelas XII IPA SMA Negeri 2 Palu - Chairunnisa, Chairunnisa; Supriadi, Supriadi; Rahman, Nurdin (Jurnal Akademika Kimia, 2017)
The research about the balancing of redox reaction on chemistry subject has been done. This research was conducted on class XII IPA8 SMA Negeri 2 Palu with 28 of the student, in the first semester of the academic year 2014-2015. The research method used is a descriptive qualitative in which data processing use percentages and rating scale. The data is collected by observation sheets, questionnaires, and documentation. Implementation of lesson study on class XII IPA8 SMA Negeri 2 Palu is conducted in three meetings time (open class) with 3 phases; plan, do and see, respectively. Based on the results obtained every meeting by the researcher, the data activity of students is rising by 54.93, 59.86, and 74.30%. Furthermore, at the third meeting, the data obtained is an excellent category which means the student’s activity in the lesson study was increased. These prove that through the lesson study can increase the activity of the learning process of students. In addition, based on the data analysis of the student’s learning outcomes during three meeting times is increased. Average of completeness of student’s learning outcomes of every meeting is 67.85, 85.71, and 100%, respectively. Again, these prove that the student’s learning outcomes by classical can be increased through the lesson study.